The Use of Song Cues for Preschool Students with Autism - Pulkrabek, Amanda J. (My University, 2012)
Individuals with autism, while under the same special education label, come into our classrooms with varying skills, differing degrees of deficit, and with a wide range of ability levels. The struggle, and sometimes the reward, of working with this population of students is how individual they are. Such a large spectrum of skills and abilities creates obstacles for professionals when determining what methods of instruction to use with each student; as a single method does not work for all. This research project looked at two different teaching strategies that can help to create success for these students throughout their day. The purpose of this study was to investigate the use of song as a cue to direct behavior for preschool students with autism. The study analyzed and compared the use of song cues in daily situations when visual supports were typically used. These daily situations include a time when a transitional cue was needed and a time when a behavioral cue was needed. Five preschool students from the same ASD classroom participated in the study. The data demonstrated that song cues were determined a successful cueing technique for preschool students with autism as supported by the data from all students during the behavioral request trials and three of the five students during the transitional request trails. This researcher was also able to determine that song cues had a lesser rate of success as compared to visual cues during the transitional request activity, but a greater rate of success during the behavioral request activity.
Keywords: preschool; Special Education; method of instruction; song cue; Educational Leadership; autism; visual cue